"Greetings from the Apocalypse": Race, Migration, and Fear after German Reunification. Issue 3 (September 2021) - Molnar, Christopher A.
Abstract: In the early 1990s, reunified Germany faced surging numbers of asylum seekers and a wave of far-right violence against foreigners. In letters that German citizens wrote to President Richard von Weizsäcker, it is clear that some Germans feared that the arrival of large numbers of non-Germans would bring about the collapse of the state or the destruction of the German people. This article engages with the history of fear in postwar Germany by examining Germans' post-reunification fears of migration and foreigners. I argue, first, that a biological understanding of race was still surprisingly widespread as late as the early 1990s. Second, I call for a substantially more nuanced understanding of German reunification, one that emphasizes uncertainty and the terrifying openness of the future. Finally, I highlight the intersection of race thinking and memory by showing that racial fears were frequently shaped by memories of Germany's dark past.